2019
DOI: 10.1002/eap.1997
|View full text |Cite
|
Sign up to set email alerts
|

Fire‐mediated habitat change regulates woodland bird species and functional group occurrence

Abstract: In an era characterized by recurrent large wildfires in many parts of the globe, there is a critical need to understand how animal species respond to fires, the rates at which populations can recover, and the functional changes fires may cause. Using quantified changes in habitat parameters over a~400-yr post-fire chronosequence in an obligate-seeding Australian eucalypt woodland, we build and test predictions of how birds, as individual species and aggregated into functional groups according to their use of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 49 publications
(196 reference statements)
3
11
2
Order By: Relevance
“…Neither the richness nor abundance of hollow-nesting birds was related to time since fire in this study. This result contrasts with a study in a semi-arid Eucalyptus woodland dominated by obligate-seeding trees (Gosper et al, 2019) that showed a strong influence of time since fire on the abundance of hollow-nesting birds.…”
Section: How Do Bird and Plant Communities Change With Time Since Fire?contrasting
confidence: 99%
“…Neither the richness nor abundance of hollow-nesting birds was related to time since fire in this study. This result contrasts with a study in a semi-arid Eucalyptus woodland dominated by obligate-seeding trees (Gosper et al, 2019) that showed a strong influence of time since fire on the abundance of hollow-nesting birds.…”
Section: How Do Bird and Plant Communities Change With Time Since Fire?contrasting
confidence: 99%
“…Guild-level responses to fire disturbance have been reported in other studies in Australia (Turner 1992;Loyn 1997;Davis et al 2016;Gosper et al 2019b) and elsewhere (Barlow & Peres 2004). The apparent negative fire response shown by the insectivore and frugivore/granivore guilds in the present study probably reflects loss and successional recovery of foraging habitat and is similar to the findings of Davis et al Overall difference probability value (chi-squared goodness of fit -7 years pooled) and temporal difference probability value (chi-squared contingencyyears 1, 4 and 7): *P < 0.05, **P < 0.01, ***P < 0.001.…”
Section: Discussionsupporting
confidence: 71%
“…First, the primary effects of fire are indirect through habitat change, which is caused by both individual fires and by different fire regimes. This has been shown for many biomes for a wide range of animal taxa, including ants (Andersen, 2019), reptiles (Costa et al, 2020;Dixon et al, 2018), birds (Gosper et al, 2019;Woinarski & Recher, 1997) and small mammals (Griffiths & Brook, 2014). In particular, fire has a pervasive effect on fauna through its impact on habitat openness (Andersen, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…However, severe fire causes major habitat transformation, initiating a long-term series of habitat changes that successively favour different animal species (Fox, 1990;Gosper et al, 2019;Lindenmayer et al, 2016Lindenmayer et al, , 2019. A feature of such forests is the occurrence of old-growth specialists that are often under conservation threat because of habitat fragmentation and inappropriate burning or logging (Chalmandrieret al, 2013;Dixon et al, 2018Dixon et al, , 2019Lindenmayer et al, 2017;Taylor et al, 2012).…”
Section: Discussionmentioning
confidence: 99%